2021
DOI: 10.17645/si.v9i4.4476
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Life Trajectories on Retirement: Socioeconomic Differences in Social Support Networks

Abstract: In general, the literature about social support networks (SSNs) has been divided into two different statements: On the one hand, social support is a safety net that helps the ego confront disadvantages in life. On the other hand, studies have shown how SSNs could act as sources of constraints for ego, especially in poverty. In this study, we looked into the SSNs of older people over time and found how those two paths co‐exist and depend on the socioeconomic status of ego. Then, this article aims to discover ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A classic study by Antonucci and Akiyama (1987) found critical differences in the way older individuals experienced their SSNs, which were ascertained to be a function of the gender of the person. In this article, there were no differences by gender, although gender variances were found in the frame of the same research Ortiz & Bellotti, 2021).…”
Section: Discussionmentioning
confidence: 49%
“…A classic study by Antonucci and Akiyama (1987) found critical differences in the way older individuals experienced their SSNs, which were ascertained to be a function of the gender of the person. In this article, there were no differences by gender, although gender variances were found in the frame of the same research Ortiz & Bellotti, 2021).…”
Section: Discussionmentioning
confidence: 49%